Rancang Bangun Sistem Tabungan Bank Minyak Jelantah Berbasis Web (Studi Kasus PT.Hijau Solusi Utama) - Ilham Maulana; Yono Cahyono (CV. Multi Kreasi Media, 2023)
PT. Hijau Solusi Utama is a company engaged in the management of inorganic waste and used cooking oil. Used cooking oil is waste oil that comes from types of cooking oil such as corn oil, vegetable oil, and so on. This oil is generally used for household needs, can be reused for culinary purposes. The problem that occurs at this time is that there are still a lot of used cooking oil bank savings data that use a manual system (In inputting data the user still uses a passbook and for pick-up requests he still uses via whatsapp to the admin) and data collection of used cooking oil savings still occurs invalid data between admins and the collection of used cooking oil as well as the lack of use of web-based technology used by PT. Hijau Solusi Utama for managing cooking oil bank savings. There are several methods used in this research, namely the observation method, interview method, and literature study. In addition, in developing the application system using the waterfall method, a system development method where one phase to another is carried out sequentially. The result of this research is in the form of a cooking oil bank savings system. Admins can easily input used cooking oil savings data and officers can easily pick up used cooking oil by using a QR Code scan. Users can also easily make requests to pick up used cooking oil and withdraw savings from used cooking oil. This system was developed using PHP Native programming language, MYSQL database as data storage and XAMPP server application.